الإيقاع الزمني في رواية اختفاء لهشام مطر (Comprehensive Journal of Science, 2025)
Temporal Rhythm in Hisham Matar's " disappearance"Time is an essential element in the structure of a novel; it contributes to shaping its world and acts as the backbone that connects its various parts. It serves as the framework within which events unfold and characters move. This paper aims to shed light on the temporal rhythm in the novel *disappearance* by the Libyan-British writer Hisham Matar, focusing on the different techniques of rhythm and the narrative functions that result from using these techniques.Matar demonstrates remarkable artistic skill in varying the narrative rhythm. The novel is rich in this diversity, as he sometimes employs techniques and strategies to accelerate the narrative pace, such as *summary* and *ellipsis*, and at other times, he resorts to slowing down or halting narrative time through the use of *scene* and *descriptive pause*. This study explores the semantic, aesthetic, and artistic dimensions of each of these different patterns..